Modern views on the acquisition of technological advantage in the course of repelling large-scale armed aggression, taking into account the proportionality of adversary countries - Koval, Volodymyr; Semenenko, Oleh; Baranov, Serhii; Ostrovskyi, Serhii; Akinina, Tetiana; Dobrovolskyi, Yuzef (Social Development and Security, 2023)
Purpose: to form modern views on the acquisition of technological advantage in the course of repelling large-scale armed aggression, taking into account the proportionality of the adversary countries, with an emphasis on the need for the formation of technological advantage of Ukraine in the war against Russia as the main way to resolve the conflict. Method: the main methods of research are methods of analysis and synthesis, methods of induction and deduction, methods of expert survey. Findings: the main aspects of research on the acquisition of technological advantage are determined, taking into account the main challenges and limitations regarding the proportionality of opposing countries; the main requirements and principles for ensuring technological superiority over the enemy during the repulsion of large-scale armed aggression using the principle of proportionality of enemy countries were formed; formed views regarding the acquisition of a technological advantage over the enemy in the course of repelling large-scale armed aggression in the Russian-Ukrainian war in the multi-domain space; the main properties of modern wars and their manifestation in the context of the ongoing Russian-Ukrainian war are revealed; the predicted consequences of the third world war for the countries of the world are determined, and recommendations are made to reduce the probability of its occurrence. Theoretical implications: the theoretical value of the article consists in determining the formation of the main modern views on the acquisition of technological advantage in the course of repelling large-scale armed aggression, taking into account the proportionality of the adversary countries, with an emphasis on the need for the formation of technological advantage of Ukraine in the war against Russia. Paper type: methodical.